Peningkatan Kemampuan Membaca Menggunakan Metode Struktur Analitik Sitentik (SAS) pada Pembelajaran Bahasa Indonesia Kelas II MI Diponegoro - Linda Yuliana; Isna Fatimuz Zahroh; Erina Hastuti; Muflikhatul Hidayah; Nuri Afidatul Adilah (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
The objectives of this study include: To determine and describe the improvement of reading ability and through the method of Synthetic Analytical Structure (SAS) of Indonesian Lessons of students; and to determine and describe the obstacles faced by teachers in improving reading ability through the method of Synthetic Analytical Structure (SAS) of Indonesian lessons of class II students of MI Diponegoro Kalikudi. The type of research used is field research with a qualitative approach. Based on the results of the research that has been done, it can be concluded that: 1) Improving the ability to read Indonesian lessons through the Synthetic Analytical Structure (SAS) method in class II of MI Diponegoro, namely by preparing planning, implementing learning and evaluating learning. The planning stage includes preparing all learning tools such as RPP, while the implementation of learning includes learning activities in the classroom, and the final activity is evaluation, namely to see the extent to which students understand the learning that is being studied in this case is reading; the obstacles faced by lower class students, in this case class II, are that students have not been able to follow reading and writing learning well from the constraints of the SAS method, including: 1). The SAS method takes more time and must be more creative; 2). Causes children to memorize readings without recognizing letters; 3). Requires many facilities that must be prepared for the implementation of this SAS learning method for certain schools is considered difficult; 4). This SAS Learning Method tends to be quite difficult for children to be taught by teachers.